2005
DOI: 10.1128/iai.73.10.6860-6867.2005
|View full text |Cite
|
Sign up to set email alerts
|

Homologues of Insecticidal Toxin Complex Genes in Yersinia enterocolitica Biotype 1A and Their Contribution to Virulence

Abstract: Yersinia enterocolitica is an enteric pathogen that consists of six biotypes: 1A, 1B, 2, 3, 4, and 5. Strains of the latter five biotypes can carry a virulence plasmid, known as pYV, and several well-characterized chromosomally encoded virulence determinants. Y. enterocolitica strains of biotype 1A lack the virulence-associated markers of pYV-bearing strains and were once considered to be avirulent. There is growing epidemiological, clinical, and experimental evidence, however, to suggest that some biotype 1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 35 publications
(28 reference statements)
4
68
1
2
Order By: Relevance
“…This is in agreement with previous studies which have shown that Y. pestis and Yersinia pseudotuberculosis Tc proteins are not toxic to Sf9 insect cells, M. sexta larvae, or X. cheopis (12,13) but are active against mammalian NIH 3T3 and Caco-2 cells (12). Additionally, Yersinia enterocolitica Tc protein homologues are only mildly insecticidal and nematocidal when fed orally (33)(34)(35) but are important in colonization of the gastrointestinal tract of mice (36). In contrast, the Tc proteins of P. luminescens, the closely related Xenorhabdus nematophilus, and Yersinia entomophaga (isolated from a diseased Costelytra zealandica larva) are all highly insecticidal (3,34,37,38).…”
Section: Discussionsupporting
confidence: 81%
“…This is in agreement with previous studies which have shown that Y. pestis and Yersinia pseudotuberculosis Tc proteins are not toxic to Sf9 insect cells, M. sexta larvae, or X. cheopis (12,13) but are active against mammalian NIH 3T3 and Caco-2 cells (12). Additionally, Yersinia enterocolitica Tc protein homologues are only mildly insecticidal and nematocidal when fed orally (33)(34)(35) but are important in colonization of the gastrointestinal tract of mice (36). In contrast, the Tc proteins of P. luminescens, the closely related Xenorhabdus nematophilus, and Yersinia entomophaga (isolated from a diseased Costelytra zealandica larva) are all highly insecticidal (3,34,37,38).…”
Section: Discussionsupporting
confidence: 81%
“…Clustering based on BAPS suggests BT 1A as a separate species cluster, and given the very different nature and environment of BT 1A, this is a reasonable suggestion. Although BT 1A is considered non-pathogenic, it is isolated from healthy and ill individuals (Bottone, 1999;Tennant, Grant and Robins-Browne, 2003;Tennant, Skinner, Joe and Robins-Browne, 2005). Research shows though that the ability to cause disease and the mechanism to do so differs markedly from the other pathogenic Y. enterocolitica BT, in that survival and hibernation inside macrophages might play a role (McNally, et al, 2006).…”
Section: Yersiniamentioning
confidence: 99%
“…The toxin complex A (TCA)-like (tcaB) gene of Yersinia pestis CO92 contains a frameshift mutation, and the toxin complex B (TCB)-like (tcaC) gene contains an internal deletion (51), indicative of a loss of function, while the corresponding TCA-like and TCBlike orthologues in Y. pestis KIM and 91001 do not (18,62). Tennant et al (66) showed that mutations in each of the Yersinia enterocolitica biotype 1A T83 genes, TCA-like (tcbA), TCB-like (tcaC), and TCC-like (tccC) genes, resulted in a reduced ability to colonize the intestinal tracts of BALB/c mice compared to the wild-type strain. This suggests that the TC proteins may enhance the persistence of the host bacterium, a scenario postulated by Erickson et al (23), who found no Yersinia pseudotuberculosis TC-related toxicity toward the rat flea Xenopsylla cheopis even though expression of the TC genes is upregulated during the disease process.…”
mentioning
confidence: 99%